Ability Grouping-Based Student Placement Management in the Tahfizh Al-Qur’an Program at Senior High School - Risky Akmal Wardani; Akhmad Shunhaji; Nur Afif (Journal of Educational Management Research, 2026)
This study analyzes student placement management in the Tahfizh Al-Qur’an program through an ability grouping approach at Islamic Senior High School. Tahfizh programs represent strategic efforts to integrate Qur’anic memorization with schooling. However, their effectiveness depends on accurate placement that aligns readiness with program demands. This study used a descriptive qualitative method with a field research design. Data were collected through participant observation, in-depth interviews with school leaders, coordinators, Tahfizh teachers, counselors, homeroom teachers, and students, and documentation analysis. First, the selection process lacked standardized rubrics, written procedures, and comprehensive assessment indicators. Placement relied mainly on a brief Qur’anic reading test. Second, limited Tahfizh teacher involvement weakened diagnostic accuracy and procedural transparency. Third, inaccurate placement produced highly heterogeneous classes. Teachers consequently spent considerable time on basic tahsin rather than memorization progression. Approximately half of students failed to achieve annual memorization targets. Several students experienced academic and psychological strain. The study implies that ability grouping requires valid, transparent, and multidimensional placement instruments. It recommends integrating reading rubrics, memorization assessment, motivation interviews, and readiness questionnaires into placement policy.